A scoping review of lesbian, gay, bisexual, transgender, queer, and intersex (LGBTQI+) people's health in India - Venkatesan Chakrapani; Peter A. Newman; Murali Shunmugam; Shruta Rawat; Biji R. Mohan; Dicky Baruah; Suchon Tepjan (Public Library of Science (PLoS), 2023)
Amid incremental progress in establishing an enabling legal and policy environment for lesbian, gay, bisexual, transgender and queer-identified people, and people with intersex variations (LGBTQI+) in India, evidence gaps on LGBTQI+ health are of increasing concern. To that end, we conducted a scoping review to map and synthesize the current evidence base, identify research gaps, and provide recommendations for future research. We conducted a scoping review using the Joanna Briggs Institute methodology. We systematically searched 14 databases to identify peer-reviewed journal articles published in English language between January 1, 2010 and November 20, 2021, that reported empirical qualitative, quantitative or mixed methods data on LGBTQI+ people's health in India. Out of 3,003 results in total, we identified 177 eligible articles; 62% used quantitative, 31% qualitative, and 7% mixed methods. The majority (55%) focused on gay and other men who have sex with men (MSM), 16% transgender women, and 14% both of these populations; 4% focused on lesbian and bisexual women, and 2% on transmasculine people. Overall, studies reported high prevalence of HIV and sexually transmitted infections; multilevel risk factors for HIV; high levels of mental health burden linked to stigma, discrimination, and violence victimization; and non-availability of gender-affirmative medical care in government hospitals. Few longitudinal studies and intervention studies were identified. Findings suggest that LGBTQI+ health research in India needs to move beyond the predominant focus on HIV, and gay men/MSM and transgender women, to include mental health and non-communicable diseases, and individuals across the LGBTQI+ spectrum. Future research should build on largely descriptive studies to include explanatory and intervention studies, beyond urban to rural sites, and examine healthcare and service needs among LGBTQI+ people across the life course. Increased Indian government funding for LGBTQI+ health research, including dedicated support and training for early career researchers, is crucial to building a comprehensive and sustainable evidence base to inform targeted health policies and programs moving forward.